Traditional healer treatment of HIV persists in the era of ART: a mixed methods study from rural South Africa - Carolyn M. Audet; Sizzy Ngobeni; Ryan G. Wagner (BMC, 2017)
Abstract Background Human immunodeficiency virus (HIV) substantially contributes to the burden of disease and health care provision in sub-Saharan Africa, where traditional healers play a major role in care, due to both their accessibility and acceptability. In rural, northeastern South Africa, people living with HIV often ping-pong between traditional healers and allopathic providers. Methods We conducted 27 in-depth interviews and 133 surveys with a random sample of traditional healers living in Bushbuckridge, South Africa, where anti-retroviral therapy (ART) is publicly available, to learn: (1) healer perspectives about which HIV patients they choose to treat; (2) the type of treatment offered; (3) outcomes expected, and; (4) the cost of delivering treatment. Results Healers were mostly female (77%), older (median: 58.0 years; interquartile range [IQR]: 50-67), with low levels of formal education (median: 3.7 years; IQR: 3.2-4.2). Thirty-nine healers (30%) reported being able to cure HIV in an adult patients whose (CD4) count was >350cells/mm3. If an HIV-infected patient preferred traditional treatment, healers differentiated two categories of known HIV-infected patients, CD4+ cell counts <350 or ≥350 cells/mm3. Patients with low CD4 counts were routinely referred back to the health facility. Healers who reported offering/performing a traditional cure for HIV had practiced for less time (mean = 16.9 vs. 22.8 years; p = 0.03), treated more patients (mean 8.7 vs. 4.8 per month; p = 0.03), and had lower levels of education (mean = 2.8 vs. 4.1 years; p = 0.017) when compared to healers who reported not treating HIV-infected patients. Healers charged a median of 92 USD to treat patients with HIV. Conclusion Traditional healers referred suspected HIV-infected patients to standard allopathic care, yet continued to treat HIV-infected patients with higher CD4 counts. A greater emphasis on patient education and healer engagement is warranted.